Desenvolvimento, construção e validação de um pivô central experimental - Pazuch, Félix Augusto (2021)
Along this research, an experimental central pivot, automated with Arduino’s platform, was developed and built to meet the whole project's purposes. The developed sideline dimensioning of the pivot was carried out based on the results of distribution, as well as range and flow tests, using the selected spray model and consulting the technical manual. The validation process of the developed equipment took place during tests to evaluate the coefficient of uniformity by applying water (CUH). There were some changes among the evaluation tests regarding sideline sizing to improve the equipment efficiency. After the developed equipment has been validated, uniformity tests were carried out to apply fertilizer diluted in water used for irrigation to evaluate the correlation between water depth variable (predictive variable) and the electrical conductivity variable (response variable) and whether the CUH values of the applied water depth had influenced on CUH electrical conductivity values, under the adopted conditions to accomplish the tests. The individual performance of the sprays during uniformity tests, as well as the equipment calibration and in fertilizer application tests was evaluated by the Statistical Process Control (SPC), adopting the 𝑥̅and R control graph. Thus, the evaluation process of each spray was obtained by the process capacity value (Cp). The CUH values obtained from the uniformity tests with water application, during the equipment validation process, stabilized at 84% under the conditions and characteristics adopted for the tests, a value that corresponds to those available in bibliography in operations with commercial central pivots. The average among the tests also reached 84% in the tests with fertilizer application under the conditions and characteristics adopted for them. The Cp values for the calibration tests have suggested a high probability of the equipment, whose result for coefficient values was below 80%, which is not suitable for central pivots. These Cp values may be associated to some changes that have been made in sideline among the validation tests that resulted in high amplitude values of water depth data. The opposite occurred for the fertilizer tests, in which the sideline configurations were kept and the Cp values showed a low probability of the central pivot with coefficients below the suitable level. Taking into account all the fertilizer tests, only three of them showed significant correlation, after identifying possible outliers, and the uniformity coefficients of electrical conductivity ranged from 98 to 99%, different from the uniformity coefficient values for the solution depth, which ranged from 78 to 88%. According to the obtained results, the null hypothesis was not rejected, that is, water depth and electrical conductivity variables are independent under the conditions adopted for the studied tests. The transmitter model that was tested and used in the configurations performed better under pressures from below 1 to 1, whose distance between nozzles was 3.25 m. Under these conditions, the water depth profile, applied by the central pivot, approaches the applied average, and improves central pivot uniformity, thus, the CUH can reach values around 90%. Control charts and process capability are excellent tools for irrigated agriculture, and monitoring water depth behavior over time can be used as prediction to increase decision-making power and carry out uniformity tests.